The Effect of Household Consumption Expenditure, Government Expenditure and Per Capita Income on Economic Growth in Sidoarjo Regency - Hanum Prawita Lestari; Ignatia Martha Hendrati (UNIVED Press, 2024)
In learning to study the effect of per capita income, for economic growth in Sidoarjo Regency, pay attention to household consumption and government spending. The Central Bureau of Statistics has provided secondary data for 15 years (2007-2021) for research. IBM SPSS Version 26 program is used in multiple linear regression analysis with table α = 5% or 0.05. Based on research findings, household consumer spending, per capita income, and government spending have a significant and insignificant effect on the economic development of Sidoarjo Regency.